Discursive community and happiness in Coca-Cola advertising in times of COVID-19 - Urbina Fonturbel, Raúl; Portela Lopa, Antonio (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This article addresses the construction of a discourse community through Coca-Cola advertising, and the modifications in its persuasive discourse during the COVID-19 pandemic. Firstly, five advertisements broadcasted during the pandemic are analyzed. Subsequently, the discursive features shared by these works are delimited, which reveal the intensification of the mythical discourse, already present in a moderate way in previous campaigns. This fact allows us to fully evaluate this series of advertisements in the light of Gilbert Durand’s theories. From the formal perspective, it allows us to explain the processes of reelaboration that operate on the discursive memory present in this corpus, such as those that occur in the identification of the brand with happiness. From the referential point of view, it allows the presence of culturally recurrent symbols to be contextualized, which, influenced by circumstances, take the form of what we call the Resilience Halo.